2021
DOI: 10.1016/j.hal.2021.102010
|View full text |Cite
|
Sign up to set email alerts
|

Niche differentiation of Dinophysis acuta and D. acuminata in a stratified fjord

Abstract: Dinophysis acuta and D. acuminata are associated with lipophilic toxins in Southern Chile. Blooms of the two species coincided during summer 2019 in a highly stratified fjord system (Puyuhuapi, Chilean Patagonia). High vertical resolution measurements of physical parameters were carried out during 48 h sampling to i) explore physiological status (e.g., division rates, toxin content) and ii) illustrate the fine scale distribution of D. acuta and D. acuminata populations with a focus on water column structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 98 publications
1
35
0
Order By: Relevance
“…In Aysén, D. acuminata is endemic and blooms of variable intensity and duration occur every year between spring and autumn. D. acuminata may co-occur with D. acuta, but their niches are vertically segregated [53]. In samples with an overwhelming dominance of D. acuminata (Figure 7D) in Puyuhuapi Fjord, LC-MS analyses revealed a cellular content of PTX2 alone.…”
Section: The Dinophysis Acuminata Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In Aysén, D. acuminata is endemic and blooms of variable intensity and duration occur every year between spring and autumn. D. acuminata may co-occur with D. acuta, but their niches are vertically segregated [53]. In samples with an overwhelming dominance of D. acuminata (Figure 7D) in Puyuhuapi Fjord, LC-MS analyses revealed a cellular content of PTX2 alone.…”
Section: The Dinophysis Acuminata Complexmentioning
confidence: 99%
“…Blanco et al [54] showed that during that event, D. acuminata was present most of the time along 350 km of the coast, with cell maxima of 600-900 cells L −1 in different bays. Samples for quantitative analyses were taken with a tube sampler from 0 to 15 m. This species frequently aggregates in narrow layers close to the surface [52,53,89] and differences between 1 and 2 orders of magnitude are easily observed between tube and bottle sample counts of Dinophysis [90]. It is thus highly probable that very high concentrations of D. acuminata occurred during that event.…”
Section: The Dinophysis Acuminata Complexmentioning
confidence: 99%
“…However, in this alternative example other factors also contributed to niche differentiation between these Dinophysis species; D. acuta was associated with higher salinity compared to D. acuminata (i.e. 23-25 psu compared to 17-20 psu), and with lower levels of turbulence and Photosynthetically Active Radiation (PAR) (Baldrich et al, 2021). At each of our coastal survey sites salinity remained within 33.5-35 psu throughput the water column, so the environmental niches at our sites were not comparable with those in Chile.…”
Section: Variation In Habs In Relation To Bio-geochemical Conditionsmentioning
confidence: 93%
“…At each of our coastal survey sites salinity remained within 33.5-35 psu throughput the water column, so the environmental niches at our sites were not comparable with those in Chile. Discriminating niches for these species is important in shellfish waters, since D. acuta and D. acuminata may produce different profiles of DSP toxins (OA, DTX and PTX toxins) and profiles have been shown to vary between geographical regions (Reguera et al, 2014;Baldrich et al, 2021).…”
Section: Variation In Habs In Relation To Bio-geochemical Conditionsmentioning
confidence: 99%
“…These harmful algal blooms (HABs) mainly consist of diatoms (e.g., Pseudo-nitzschia spp.) [3], and dinoflagellates (e.g., Alexandrium catenella, Dinophysis acuta, D. acuminata, Protoceratium reticulatum, and Karenia selliformis) [1,[4][5][6]. The main causative organism of HABs is A. catenella and its negative repercussions on human health, ecosystems, fisheries, and aquaculture are well-documented [7,8].…”
Section: Introductionmentioning
confidence: 99%